Penilaian Kualitas Desain Perguruan Tinggi dengan Menggunakan Pendekatan CPTED di Kota Semarang - Dini Oktaviani Hapsari; Retno Susanti (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
The existence of Undip and Unika in Semarang become the main attraction for students who are outside Semarang. It can increase the activity around Undip and Unika areas. Nevertheless, there are some new things happening around the campus area, in September 2017, there were reports of loss of 34 motorcycles, 133 helmets and 1 rearview mirror in Undip. Meanwhile, Unika has a case of murder that killed a man outside the exit gate of Unika in 2014. Therefore to minimize the crime case it is necessary to